The Influence of Project-Based Learning Model on Improving Students' Critical Thinking Skills at SMAN Mojoagung Jombang - Khusnul Khotimah; Alex Haris Fauzi (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to examine the effect of implementing the Project Based Learning (PjBL) model on improving students’ critical thinking skills in learning Systems of Linear Inequalities in Two Variables. The study is motivated by the low level of students’ critical thinking skills in solving mathematical problems related to this topic, which requires analytical reasoning and logical conclusion drawing. The PjBL model is assumed to provide meaningful learning experiences by actively involving students in problem-solving activities, both individually and collaboratively. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed in this study. The research subjects were 36 students of class X-1 at SMAN Mojoagung. Data were collected using a critical thinking skills test administered before and after the implementation of the PjBL model. Data analysis included a normality test using the Shapiro–Wilk method and a paired sample t-test to determine the significance of differences between pretest and posttest scores.The results indicate that the application of the PjBL model significantly improved students’ critical thinking skills. The mean pretest score of 42.77 increased to 79.72 in the posttest. The normality test showed significance values of 0.053 for the pretest and 0.188 for the posttest, indicating that the data were normally distributed. Furthermore, the paired sample t-test produced a significance value of 0.000 (p < 0.05), confirming a significant difference between pretest and posttest results. These findings demonstrate that Project Based Learning is effective in enhancing students’ critical thinking skills in learning systems of linear inequalities in two variables.